2013
DOI: 10.1002/uog.12313
|View full text |Cite
|
Sign up to set email alerts
|

Maternal racial origin and adverse pregnancy outcome: a cohort study

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 53 publications
8
90
4
2
Order By: Relevance
“…15 The difference between the miscarriage rate in our study and the background rate is 0.82% which is not statistically significant. Similar difference in miscarriage rate (0.7%) has been observed in a very large study.…”
Section: Discussioncontrasting
confidence: 71%
“…15 The difference between the miscarriage rate in our study and the background rate is 0.82% which is not statistically significant. Similar difference in miscarriage rate (0.7%) has been observed in a very large study.…”
Section: Discussioncontrasting
confidence: 71%
“…However, disparities in pregnancy outcomes continue between women of differing racial or ethnic background accessing the same health-care services. [64][65][66] Stillbirth rates for women of south Asian and African origin giving birth in Europe or Australia are two to three times higher than white women. [64][65][66] The challenge is to understand why and how we can manage the excess risk of stillbirth correlated with ethnicity within routine and comprehensive antenatal care.…”
Section: Beyond Health-care Deliverymentioning
confidence: 99%
“…20 However, other data on the maternal background and obstetric outcome from the M0 data, which were based on medical records collected prospectively by physician, midwives, nurses, and trained research coordinators, are likely to be relatively accurate. Second, Khalil et al 21 reported that maternal ethnicity was related to adverse pregnancy outcomes; however, according to the JECS recruitment protocols, almost all participants in our study were Japanese women. Therefore, our results did not consider the maternal ethnicity, and the findings may not be applicable to other ethnicities.…”
Section: Discussionmentioning
confidence: 75%